A Case of Obstructing Candida Glabrata Bladder Mucus Treated with Intravesicular Amphotericin - B - Goodwin, D.O., Dr. Glenn; Gaeto, D.O., Dr. Nicholas; Seat, OMS III, Mara (International Journal of Innovative Research in Medical Science, 2021)
A 51-year-old female with a past medical history of poorly controlled diabetes mellitus presented to the emergency department with signs of emphysematous cystitis and pyelonephritis with associated Enterococcus faecalis bacteremia and Candida Glabrata (C.Glabrata) fungemia. She was treated with micafungin and amoxicillin with improvement in her symptoms. During her course she underwent repeat imaging which showed improvement in her cystitis and no obstruction in her bladder. She was discharged on home IV micafungin. She returned to the emergency department the next day with acute urinary obstruction and was found to have a completely obstructing mucus ball in her bladder. This was removed cystoscopically and surgical cultures grew C. glabrata. She was successfully treated with intra-vesicular amphotericin B and was discharged.